The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.jtcvs.2012.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year comparison of pericardial tissue valves versus mechanical prostheses for aortic valve replacement in patients younger than 60 years of age

Abstract: In the present limited cohort of patients younger than 60 years old, biologic aortic valve replacement was associated with reduced mid-term survival compared with survival after mechanical aortic valve replacement. Despite similar valve-related event rates in both groups, the better hemodynamic performance of the mechanical valves and/or protective effect of oral anticoagulation seemed to improve the outcome. The transcatheter valve-in-valve intervention as potential treatment of tissue valve degeneration shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 42 publications
4
89
1
4
Order By: Relevance
“…22 Weber et al also noted a reduced mid-term survival among patients treated with BP, with similar valve-related event rates in both age group and concluded that current evidence remains insufficient to recommend BP for AVR in patients under 60 years of age. 23 Although these data also support the present conclusions, patients treated with MP have a potential risk of bleeding events due to anticoagulation as they age. 24 Newly available anticoagulants, such as rivaroxaban and apixaban, may become strong alternatives to warfarin for reducing the rate of bleeding and thromboembolic complications associated with MP, although another new anticoagulant, dabigatran, has recently been prohibited for use in patients with MP.…”
Section: Disclosuressupporting
confidence: 79%
“…22 Weber et al also noted a reduced mid-term survival among patients treated with BP, with similar valve-related event rates in both age group and concluded that current evidence remains insufficient to recommend BP for AVR in patients under 60 years of age. 23 Although these data also support the present conclusions, patients treated with MP have a potential risk of bleeding events due to anticoagulation as they age. 24 Newly available anticoagulants, such as rivaroxaban and apixaban, may become strong alternatives to warfarin for reducing the rate of bleeding and thromboembolic complications associated with MP, although another new anticoagulant, dabigatran, has recently been prohibited for use in patients with MP.…”
Section: Disclosuressupporting
confidence: 79%
“…Weber et al found that mechanical valves (SJM or ATS bi-leaflet mechanical valves) in the aortic position were associated with better 10-year survival compared with bioprosthetic (CEP) valves in patients aged <60 years. 12 They reported that the survival advantage seemed related to the better hemodynamic performance of the mechanical valves and/or the protective effect of long-term anticoagulation. Furthermore, Brown et al reported improved long-term outcomes with mechanical valves (SJM) compared with bioprosthetic valves (CEP) in patients aged 50-70 years on propensitymatched analysis from the Mayo Clinic database.…”
Section: Discussionmentioning
confidence: 99%
“…Survival was significantly reduced in patients after biologic aortic valve replacement (90.3% vs 98%; P = 0.038) [22]. The latest trial by a Swedish group showed the same results with better long-term survival in patients aged 50-69 years after AVR with mechanical valves compared with those who had received bioprostheses.…”
mentioning
confidence: 83%